Comparison of a xenogeneic and an alloplastic material used in dental implants in terms of physico-chemical characteristics and in vivo inflammatory response - Figueiredo, Andreia (2013)
Two commercial bone grafts used in dentistry (Osteobiol Gen-Os®, a xenograft of porcine origin, and Bonelike®, a hydroxyapatite based synthetic material), in the form of granules, were characterized and evaluated in vivo regarding the intensity of the tissue inflammatory response. These biomaterials were characterized in terms of morphology, particle size distribution, porosity and pore size, specific surface area and density. The chemical composition and structure of the materials were accessed by Fourier-Transform Infrared Spectroscopy (FTIR) and X-ray Diffraction (XRD). The graft materials were implanted in the gluteus maximus muscles of Wistar rats and the inflammatory response was evaluated through histological analysis, after one week of implantation. The results showed that the two grafts have quite different characteristics in practically all the evaluated properties. While Osteobiol® exhibits a structure and composition similar to the natural bone, Bonelike® is constituted by a main crystalline phase of hydroxyapatite and two secondary phases of α- and β-tricalcium phosphate. Osteobiol® granules, besides being larger, are irregular, and exhibit sharp-edged tips, while those of Bonelike® are approximately cylindrical, with round contours, and more uniform in size. The in vivo response evaluated from the inflammatory infiltrates revealed that although both implants did not cause severe inflammation, Bonelike® granules elicit a consistently more intense inflammatory reaction than that triggered by the granules of Osteobiol®, particularly in terms of collagen production and formation of fibrous capsule. This reaction was partly explained in terms of the characteristics evaluated for the granules of this material.